A Case Study on Farmers’ Literacy in Agriculture Information in Lunglei District, Mizoram - Ruth Lalthlamuanpuii; Jopir, Jyoti (Indian Journal of Extension Education, 2024)
G Many farmers in Lunglei District depend on agriculture for their living, therefore urban residents also depend on agricultural produce. Due to the development of technology, farmers today have easy access to a variety of information that they can use in their farming. However, they still need to know where to turn for reliable data that they can use.The present study adopted a quantitative research method for accessing the information on literacy awareness among 150 agricultural farmers in selected 30 villages in Lunglei District, Mizoram during the year 2020-2023.The majority of the farmers claimed to be information literate, the findings show that farmers lacked information literacy abilities. Farmers rely heavily on the information they learn from other people, have poor reading abilities, and are unable to search the information they require. The use of media has been discovered to be the most effective platform for farmers to acquire information and farmers primarily seek information to determine whether forecasts are accurate. The result suggested that farmers must be instructed on how to improve their information literacy abilities by Government officials and library professionals.